Seni sebagai Pelarian ke dalam Kepribadian Lain: Sebuah Eksperimen Pembacaan Jauh atas Dua Marga - Suryajaya, Martin (Urban: Jurnal Seni Urban, 2022)
In his recent poetry book, Dua Marga (2022), Nirwan Dewanto experimented with writing poetry through two heteronyms as an attempt to escape from his personality. This article is an experiment on distant reading of that book with the aim of testing the extent to which the voice separation between the two heteronyms is realized. The distant reading method used here focuses on analyzing the frequency and co-occurrence of words and interpreting words as vectors so that the degree of similarity of a set of words can be calculated as the distance between vectors. Based on this analysis, it is found that Dua Marga’s poems do not show any grouping into the two heteronyms; there is a significant confounding between the two. In addition, anomalies were also found in a number of poems indicating the existence of a ‘third voice’ in the Dua Marga. On that basis, a new interpretation will be explored regarding the escape from personality as an artistic project.Dalam buku puisi, Dua Marga (2022), Nirwan Dewanto bereksperimen menulis puisi melalui dua heteronim sebagai amalan dari upaya pelarian diri dari kepribadian. Artikel ini merupakan sebuah eksperimen pembacaan jauh atas buku puisi tersebut dengan tujuan menguji sejauh mana terwujud separasi suara antara kedua heteronim tersebut. Metode pembacaan jauh yang digunakan di sini berfokus pada analisis frekuensi dan ko-okurensi kata serta dengan mengartikan kata sebagai vektor sehingga tingkat kemiripan sebuah himpunan kata dapat dihitung sebagai jarak antarvektor. Berdasarkan analisis ini ditemukan bahwa puisi- puisi Dua Marga tidak menunjukkan pengelompokan ke dalam kedua heteronim; terdapat pembauran yang cukup signifikan antara keduanya. Selain itu, ditemukan pula anomali pada sejumlah puisi yang mengindikasikan keberadaan ‘suara ketiga’ dalam Dua Marga. Atas dasar itu, sebuah pemaknaan baru akan dijajaki mengenai pelarian dari kepribadian sebagai proyek artistik.